Becoming a Developer: Processes of Personhood in Urban Community-driven Development, Indonesia. Issue 3 (3rd July 2017) - Jakimow, Tanya
ABSTRACT: Community-driven development in Indonesia requires the recruitment of volunteers: local residents with the will to develop themselves and others. By revealing the processes of personhood in light of volunteers' own theories of self, I aim to disrupt simple readings of subjectification in the anthropology of development. Local volunteers understand their recruitment as having the opportunity to occupy a social position that is aligned with their jiwa (nature), and their participation as satisfying their hati (seat of emotion). Rather than assess the success or failure of state actions to regulate or constitute citizens through discursive and affective means, I take seriously this understanding of development as a process of locating and recruiting people predisposed to becoming the subjects of state development. Doing so prompts new lines of enquiry that have been overlooked in understanding processes of subjectification in development: namely the reason why some people are recruited as development subject, while the majority are not.